How to choose the best promotion strategies for increasing prospective students: The role of risk management factors - Kusuma, Yudha Adi (Universitas Sultan Ageng Tirtayasa, 2023)
X University is one of the private universities located in the East Java province. To retain prospective students and encourage them to register, informational media through promotion is necessary. To determine the best promotion strategy, student profile data is utilized. The accumulated student profile data must be processed through data mining. In this research, the K-means method is used for data mining. The K-means measurement results are divided into three groups: Cluster 1 includes P1, P7, and P8; Cluster 2 includes P2 and P9; and Cluster 3 includes P3, P4, P5, P6, and P10. The risk management process is carried out in three stages: risk identification, risk assessment, and risk mitigation. The results of the risk identification phase showed that there were 15 risk variables. The risk assessment phase revealed two very high category risks, two high category risks, four medium category risks, and seven low category risks. Following the advice of X University, risk mitigation activities were selected for the very high and high-category risk variables. The results of this research are expected to contribute to an increase in the number of students at X University in the future.